Enabling Efficient Genetic Manipulations in a Rare Actinomycete Pseudonocardia alni Shahu - Li, Jie; Wang, Baiyang; Yang, Qing; Si, Han; Zhao, Yuting; Zheng, Yanli; Peng, Wenfang (Frontiers in Microbiology, 2022)
Pseudonocardia species are emerging as important microorganisms of global concern with unique and increasingly significant ecological roles and represent a prominent source of bioactive natural products, but genetic engineering of these organisms for biotechnological applications is greatly hindered due to the limitation of efficient genetic manipulation tools. In this regard, we report here the establishment of an efficient genetic manipulation system for a newly isolated strain, Pseudonocardia alni Shahu, based on plasmid conjugal transfer from Escherichia coli to Pseudonocardia. Conjugants were yielded upon determining the optimal ratio between the donor and recipient cells, and designed genome modifications were efficiently accomplished, including exogenous gene integration based on an integrative plasmid and chromosomal stretch removal by homologous recombination using a suicidal non-replicating vector. Collectively, this work has made the P. alni Shahu accessible for genetic engineering, and provided an important reference for developing genetic manipulation methods in other rare actinomycetes.